2018
DOI: 10.1039/c8sm00080h
|View full text |Cite
|
Sign up to set email alerts
|

Glassy worm-like micelles in solvent and shear mediated shape transitions

Abstract: The glassiness of polymer melts is generally considered to be suppressed by small dimensions, added solvent, and heat. Here, we suggest that glassiness persists at the nanoscale in worm-like micelles composed of amphiphilic diblock copolymers of poly(ethylene oxide)-polystyrene (PS). The glassiness of these worms is indicated by a lack of fluorescence recovery after photobleaching as well as micron-length rigid segments separated by hinges. The coarse-grained molecular dynamics studies probe the dynamics of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…Initially, the SPAM method (maps spelled in reverse) was applied to calculate the relative free energy difference between water molecules at the protein surface from the distribution of interaction energies between the water molecules and the environment . Later, we also used this method to calculate the relative free energy of an encapsulated hydrophobic solvent in diblock copolymer micelles . According to this method, the free energy of an ion can be represented as G SPAM = − RT ln Q SPAM ; Q SPAM is the partition function defined as Q SPAM = ∑ ES [ P ( E I ) exp­(− E I / RT )], where P ( E I ) is the probability of a ion having interaction energy E I with its surroundings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Initially, the SPAM method (maps spelled in reverse) was applied to calculate the relative free energy difference between water molecules at the protein surface from the distribution of interaction energies between the water molecules and the environment . Later, we also used this method to calculate the relative free energy of an encapsulated hydrophobic solvent in diblock copolymer micelles . According to this method, the free energy of an ion can be represented as G SPAM = − RT ln Q SPAM ; Q SPAM is the partition function defined as Q SPAM = ∑ ES [ P ( E I ) exp­(− E I / RT )], where P ( E I ) is the probability of a ion having interaction energy E I with its surroundings.…”
Section: Discussionmentioning
confidence: 99%
“…The number of EO (ethylene oxide) monomers, N EO , plus the number of hydrophobic monomers, N h , gives N total = N EO + N h , and one can calculate f EO = N EO m EO /( N EO m EO + N h m h ), where the m i ’s are the monomer masses that establish the total molecular weight of the polymer M tot . Previously, we have shown that this PEO–PS model with different copolymer lengths can also describe the characteristic partitioning of model hydrophobic solvents in the micellar phase . The CG parameters for PEO were originally developed by Shinoda et al The CG parameters for PS are developed by our laboratory using the Shinoda–DeVane–Klein (SDK) CG methodology.…”
Section: Simulation Detailsmentioning
confidence: 99%
“…It also enables a versatile way for constructing highly effective vehicles for the cellular delivery of biomolecular cargo. synthetic polymers [7] have been used to create supramolecular assemblies with different morphologies and functions by utilizing non-covalent interactions and stimuli such as pH, [8] electrolyte concentration, [9,10] solvent switching, [11][12][13] chemical, and enzymatic reactions, [8,[14][15][16] shear forces, [17] seeding, [18,19] light, [20] and temperature. [13,21,22] Especially the latter stimulus has been applied extensively both in natural and synthetic systems.…”
Section: Introductionmentioning
confidence: 99%
“…Self‐assembly is an intriguing phenomenon found in nature that chemists are increasingly able to employ in order to create supramolecular smart materials. Information‐rich natural building blocks based on DNA, [ 1,2 ] peptides/proteins, [ 3–6 ] and synthetic polymers [ 7 ] have been used to create supramolecular assemblies with different morphologies and functions by utilizing non‐covalent interactions and stimuli such as pH, [ 8 ] electrolyte concentration, [ 9,10 ] solvent switching, [ 11–13 ] chemical, and enzymatic reactions, [ 8,14–16 ] shear forces, [ 17 ] seeding, [ 18,19 ] light, [ 20 ] and temperature. [ 13,21,22 ] Especially the latter stimulus has been applied extensively both in natural and synthetic systems.…”
Section: Introductionmentioning
confidence: 99%
“…The relatively large fluctuations in Rg for both systems are due to the dynamic processes of micelle formation in the aqueous media. Relevant papers include [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30].…”
mentioning
confidence: 99%